Materials for Digital Dentistry - Dagtekin, Aybike Cengiz; Tekin, Samet; Eser, Bekir; Khurshid, Zohaib; Khurshid, Zohaib; Ashi, Heba (CRC Press, 2026)
With the continuous development of digital production in dental area, distinct substances are used periodically. Metals, composite resins, and ceramics are used to fabricate restorations and appliances. Digital methods increase patient-physician comfort. The properties of the materials used may differ from those of restorations prepared using subtractive and additive manufacturing methods. It is crucial to be aware of these differences in material and production preferences. Additive production is turning into an alternative to subtractive production for many applications. Research that shows the clinical effect of the materials used in additive manufacturing is also increasing. © 2026 selection and editorial matter, Zohaib Khursid, Muhammad Sohail Zafar, and Dinesh Rokaya; individual chapters, the contributors.
Keywords: Additives; Dentistry; Industrial research; Clinical effects; Composite ceramic; Composite resins; Continuous development; Digital methods; Digital production; Manufacturing IS; Manufacturing methods; Metal composites; Property; Clinical research